Effect of high-energy ball milling and silica fume addition in BaCO 3- Al 2 O 3. Part I: Formation of cementing phases - Kumar P.H.; Srivastava A.; Kumar V.; Kumar P.; Singh V.K. (My University, 2025)
The effects of high-energy ball milling and subsequent calcination on the formation of barium aluminate cementing phases using mixtures of Al2O3 and BaCO3 were investigated. Silica fume was further added in the raw mixtures to observe its role on the cementing phase formation. Results indicated that the decomposition temperature of BaCO3 lowered remarkably with the increase in milling time. Barium aluminate cements with grain size in nanometer range were obtained from high-energy ball-milled raw mixtures. X-ray diffraction (XRD) results confirmed several crystalline barium-silicate and barium aluminate phases present. Formation of crystalline BaO·Al2O3 phase was observed between 1000°C and 1100°C in the raw mixtures, which were obtained in amorphous state after milling for 5 h. This temperature is at least 300°C lower than that used in the traditional solid-state method. Fume SiO2 additions resulted in BaO·Al2O3·2SiO2 (celsian) formation which acted as a retarder, provides more workability and mechanical strength. © 2014 The American Ceramic Society.